A multi-attribute based trusted routing for embedded devices in MANET-IoT - Feroz Khan, A.B.; R, Hannah Lalitha; S, Kalpana Devi; CN, Rajalakshmi (Microprocessors and microsystems, 2022)
High level security is always an important requirement to save the sensitive information traveled across the MANET-IoT. Secure routing is one of the major concerns to prevent impersonation attacks from the network. There are many state of the art routing model available based on trusted metrics to enhance the security of the MANET-IoT. However, still there are many challenges to provide high secure environment due to the dynamic characteristics of the network. In this paper, an enhanced multi attribute based attack resistance (EMBTR) algorithm is proposed to perform the routing process securely based on nodes’ trusted values. The work proposed here uses QoS parameters such as stability rate (SR), reliability rate (RR), and elapsed time (ET) to enhance the performance of the network by combating trust related attacks. The algorithm introduced in the paper can provide a trustworthy route by isolating the misbehavior nodes from the communication path based on the trusted metrics calculated for the nodes in the network. The proposed work is compared with currently available routing algorithms such as TSRM (Trust based secure routing model), and TARF (Trust-aware routing framework for WSNs). The result shows that the proposed work can efficiently detect and remove malicious nodes from the network and provide secure routing with limited energy, and high detection rate than the currently available solutions.